ACCUMULATION RATE ON THE ICE SHEET SURFACE IN EAST QUEEN MAUD LAND, EAST ANTARCTICA - タカハシ, シュウヘイ; TAKAHASHI, Shuhei (National Institute of Polar Research, 1991)
P(論文) In the East Queen Maud Project from 1981 to 1987,accumulation rate on the ice sheet surface was observed in an extensive inland area by the stake-method. Along a traverse route from Syowa Station (69°00'S, 39°35'E, 21m a. s. l.) to Dome Camp (77°00'S, 35°00'E, 3761m a. s. l.), variation of accumulation rate with elevation was obtained. The accumulation rate was large (about 50cm/a snow depth) in the lower part of ice sheet between 800m and 1500m a. s. l., small (about 15cm/a) in the middle part between 2000m and 2400m, and intermediate (about 30cm/a to 20cm/a) in the higher part above 2400m. Redistribution of drifting snow was estimated by a calculation of drifting snow convergence, based on the dependence of katabatic wind speed on topography and the relation between drifting snow and wind speed. The calculated convergence was large positive at around 800m a. s. l., negative between 2000m and 2400m a. s. l., and negligibly small above 2400m a. s. l., Taking account of this drifting snow convergence into the accumulation rate, the observed variation of accumulation rate with elevation was well explained. departmental bulletin paper